Neutrophil-Derived IL-17 Promotes Ventilator-Induced Lung Injury via p38 MAPK/MCP-1 Pathway Activation - Liao, Xiaoting; Zhang, Weikang; Dai, Huijun; Jing, Ren; Ye, Mengling; Ge, Wanyun; Pei, Shenglin; Pan, Linghui (Frontiers in Immunology, 2021)
Ventilator-induced lung injury (VILI) is one of the most common complications of mechanical ventilation and can severely affect health. VILI appears to involve excessive inflammatory responses, but its pathogenesis has not yet been clarified. Since interleukin-17 (IL-17) plays a critical role in the immune system and the development of infectious and inflammatory diseases, we investigated here whether it plays a role in VILI. In a mouse model of VILI, mechanical ventilation with high tidal volume promoted the accumulation of lung neutrophils, leading to increased IL-17 levels in the lung, which in turn upregulated macrophage chemoattractant protein-1 via p38 mitogen-activated protein kinase. Depletion of neutrophils decreases the production IL-17 in mice and inhibition of IL-17 significantly reduced HTV-induced lung injury and inflammatory response. These results were confirmed in vitro using RAW264.7 macrophage cultures. Our results suggest that IL-17 plays a pro-inflammatory role in VILI and could serve as a new target for its treatment.